Currency swaps - Coyle, Brian; Chartered Institute of Bankers (Canterbury : Financial World Pub., 2000)
An introduction to equity, commodity and credit swaps. The text describes the evolution of this financial instrument and the present day importance it has in debt and interest rate risk management. It examines the features of currency swaps and the process by which the counterparties reach agreement. Through practical examples it illustrates the role of banks and explains swaps pricing and the value of a swap.
Previous ed.: London : BPP Financial, 1994.
Includes bibliographical references and index.
oif 16/07/14
Loan
Keywords: Currency swaps